ChemInform Abstract: A Novel Oxy‐Oxonia(Azonia)‐Cope Reaction: Serendipitous Discovery and Its Application to the Synthesis of Macrocyclic Musks. Issue 52 (29th December 2014) - Zou Yue, Zou Yue; Zhou, Lijun; Ding, Changming; Wang, Quanrui; Kraft, Philip; Goeke, Andreas
Abstract Review: 43 refs.